ADAPTATION OF MYTHOLOGICAL IMAGES OF UKRAINIAN FOLKLORE IN THE COMPOSITION OF ART AND DESIGN WORKS IN THE CONTEXT OF HISTORICAL DEVELOPMENT - Slityuk , Olena; Lunko, Alina; Sklyarenko, Sklyarenko Valerij; Lavrusenko, Serhii (Theory and practice of design, 2025)
The purpose. The study explores the evolutionary development of the use of Ukrainian mythological imagery in artworks and design, aiming to identify the adaptability of folkloric motifs to the demands of the contemporary graphic environment as a means of visual-aesthetic communication. Methodology. The research applies a comprehensive approach that includes the analysis of academic literature, specific artworks, and design projects reflecting the adaptation of mythological imagery within the modern cultural landscape of Ukraine. Results. The study examines and analyzes the historical aspects of the use of mythological motifs in visual art, which made it possible to establish the evolutionary nature of the visual representation of folkloric characters – from decorative illustrations in folk art and Soviet graphic design to deeply conceptualized images in national branding and communicative design. It was found that archetypes embodied in graphic images are adapted to current social contexts while retaining their ethnocultural significance. The study also investigates the use of mythological motifs in animated advertising, revealing their role as a powerful narrative and emotional tool in branding. The scientific novelty. The psychological aspects of perceiving traditional characters in digital marketing were analyzed, allowing the conclusion that they are capable of generating deep emotional responses. Practical relevance. The results of the study may be utilized by designers, developers, and digital content specialists to create visually appealing and culturally significant projects.